Malignant melanoma of breast: a case report - Bhagyalakshmi, A.; Uma, P.; Sri, K. Satya; Kumar, S. V. (International Journal of Research in Medical Sciences, 2017)
Malignant melanoma rarely affects the breast. Malignant melanoma of breast is divided into two categories: primary and metastatic lesions. Primary melanoma involves the skin and less commonly the glandular parenchyma of the breast. Differentiating them is very important in deciding on treatment strategies. This case report aims to increase awareness of unusual neoplasms of the breast which requires a different surgical and adjuvant therapeutic approach.